IMPROVING THE QUALITY OF BREAD USING CASSAVA FLOUR SUBSTITUTION AND α-AMYLASE - khusniati, tatik; Purnamasari, Elisa; Effendi, Supli; Anindyawati, Trisanti (Teknologi Indonesia, 2016)
Bread in Indonesia generally used wheat flour as a basic material and it is an imported flour product up to now. On the other hand, cassava flour can be used as wheat flour alternative for substitution. This research was aimed to improve the quality of bread using cassava flour substitution and α-amylase. Variables used were wheat and cassava flour with comparison: 100:0, 95:5, 90:10, 85:15, and α-amylase with concentration: 0, 0.5, 1.0, 1.5%, respectively. The contents of water, ash, protein, carbohydrate, and salt were determinated by modifying the AOAC method. The pH of bread dough was measured and α-amylase activities were determined by Iodine method. The dough and substituted-bread volumes were measured, and organoleptic tests were conducted by training 20 panelists. Statistical analysis used factorial completely randomized experimental design (FCRD). The results show that the highest values of water, ash, protein and carbohydrate were found in bread of A4B2 (25.13%), A1B1 (0.97%), A1B2 (8.62%), A4B2 (47.89%), sequentially (P<0.05). A2B4 was bread with the best organoleptic value and biggest volume than the others with nutritional contents of water (25.10%), ash (0.87%), protein (7.98%), carbohydrate (46.89%), and salt (2.17%). The values of these nutritional contents was in scope of bread SNI standard. Cassava flour substitution and α-amylase affected significantly to organoleptic values of bread produced (P<0.05). The α-amylase activities of all treated bread were not significantly different (P<0.05). Based on volumes of bread dough and bread as well as organoleptic tests, the best bread is A2B4 (95% wheat flour using 5% cassava flour and 1.5% α-amylase).